SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MAKANAN UNTUK PENDERITA PENYAKIT KOLESTEROL DENGAN MENGGUNAKAN METODE ANALITYCAL HIERARCHY PROCESS (AHP) - Nuraisana Nuraisana (Jurnal Mantik Penusa, 2018)
Cholesterol disease affects many people only, but does not rule out the possibility of cholesterol can also be suffered by thin people as well. However this does not mean that cholesterol is "bad" can not be avoided. The choice of dietary patterns is very necessary for people with cholesterol because it can reduce or prevent high cholesterol levels. The design of a decision support system application uses the Analyticalcal Hierarchy Process (AHP) method, using calorie, protein and charcoal hydrate criteria that are changed in the form of weighted assessments so that the system can perform calculations that provide speed of information in the form of a computerized system that is expected to help sufferers of cholesterol to knowing which foods are suitable for daily consumption. Decision support systems provide results in the form of information printed in the form of reports containing food data suitable for sufferers of cholesterol based on the highest value to the lowest value, thus providing convenience for patients to manage their daily eating patterns